The rate of de novo structural variation is increased in in vitro–produced offspring and preferentially affects the paternal genome - Lee, Young-Lim; Bouwman, Aniek C.; Harland, Chad; Bosse, Mirte; Costa Monteiro Moreira, Gabriel; Veerkamp, Roel F.; Mullaart, Erik; Cambisano, Nadine; Groenen, Martien A.M.; Karim, Latifa; Coppieters, Wouter; Georges, Michel; et al. (Genome Research, 2023)
Assisted reproductive technologies (ARTs), including in vitro maturation and fertilization (IVF), are increasingly used in human and animal reproduction. Whether these technologies directly affect the rate of de novo mutation (DNM), and to what extent, has been a matter of debate. Here we take advantage of domestic cattle, characterized by complex pedigrees that are ideally suited to detect DNMs and by the systematic use of ART, to study the rate of de novo structural variation (dnSV) in this species and how it is impacted by IVF. By exploiting features of associated de novo point mutations (dnPMs) and dnSVs in clustered DNMs, we provide strong evidence that (1) IVF increases the rate of dnSV approximately fivefold, and (2) the corresponding mutations occur during the very early stages of embryonic development (one- and two-cell stage), yet primarily affect the paternal genome.